Élaboration de composites verre de phosphate de zinc/ graphite : modélisation et étude expérimentale des paramètres de transport thermoélectriques - Nassima RADOUANE (Faculté des Sciences de Rabat, 2021)
The research carried out in the framework of this thesis has consisted in the development of zinc phosphate glass (45mol. %ZnO-55mol. %P2O5) based composites, loaded by different graphite fractions, to study their thermoelectric properties. The structural characterizations of the obtained composites were carried out using different techniques such as X-ray Diffraction (DRX), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Then, their thermoelectric transport parameters were determined by measuring the following physical quantities: the electrical conductivity (σ), the thermal conductivity (κ) and the Seebeck coefficient (S). The obtained results were fitted using effective medium theory for each parameter. Based on these results, the figure of merit (ZT=σS2T/κ) quantifying the thermoelectric performance of the elaborated composites was calculated as a function of graphite concentration. This study showedthat the figure of merit depends on the volumique concentration of graphite and shows a maximum at 5 vol.%. A signature of a percolation mechanism was observed on both the effective electrical conductivity σ and the effective κ/S ratio. A shift in percolation thresholds between each of these effective parameters was observed. We have demonstrated that the observed maximum in ZT value is due to this shift. To explain this behavior, we suggest an electrical conduction mechanism by a tunneling effect between graphitic clusters.
Elaboration of zinc phosphate glass/graphite composites: modeling and experimental study of thermoelectric transport parameters
Keywords: Science Des Matériaux; Science Des Matériaux